The conducting form of gramicidin A is a right-handed double-stranded double helix - Burkhart, B. M. (The National Academy of Sciences, 1998)
The linear pentadecapeptide antibiotic, gramicidin D, is a naturally occurring product of Bacillus brevis known to form ion channels in synthetic and natural membranes. The x-ray crystal structures of the right-handed double-stranded double-helical dimers (DSDH(ℛ)) reported here agree with (15)N-NMR and CD data on the functional gramicidin D channel in lipid bilayers. These structures demonstrate single-file ion transfer through the channels. The results also indicate that previous crystal structure reports of a left-handed double-stranded double-helical dimer in complex with Cs(+) and K(+) salts may be in error and that our evidence points to the DSDH(ℛ) as the major conformer responsible for ion transport in membranes.